(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2021)
This piece is essentially a conversation between "True Love" and "The Loch Ness Monster". The dialogue encapsulates the pursuit of True Love and the circumstances that follow that particular pursuit. The mythical creature, in this case, questions True Love about its existence and is guided through the Socratic method to a vision that prompts action and growth. For additional context, listen to the author’s reflection on the piece below.